Pengaruh Kesejahteraan Karyawan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di Pt. Indo Veneer Utama Surakarta Tahun 2015. - Widowati, Bella Dyah Dika; , Dra. Titik Asmawati, SE, M.Si (2015)
ABSTRACT Bella Dyah Dika W. / A210110106; WELFARE EFFECT OF EMPLOYEES AND WORKING ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES IN PT. INDO VENEER Surakarta YEAR 2015 HIGHLIGHTS Thesis, Faculty of Teacher Training and Education, University of Muhammadiyah Surakarta. September, 2015 The purpose of this study was to determine the effect of: 1) the welfare of employees on employee performance, 2) the work environment on employee performance, 3) the welfare of employees and the work environment on employee performance. This research is a descriptive quantitative research. The research population is all employees amounted to 290 people with a sample of 158 employees were taken by simple random sampling technique. Data collected by questionnaire. Questionnaire tested the validity and reliability as well as test requirements dilkakukan data analysis technique used is multiple linear regression analysis, t test, F test, ujiR2dansumbangan relatively and effectively. The research found that: 1) there is positive and significant influence on employee performance employee benefits evidenced by 0.526 regression coefficient is positive and obtained t> t table is 6.385> 1.984 and the significance value <0.05 is 0.000 <0.05; 2) no positive and significant impact on the performance of the employee work environment evidenced by 0.536 regression coefficient is positive and obtained t> t table is 6.164> 1.984 and the significance value <0.05 is 0.000 <0.05; 3) there is a significant positive influence and welfare of employees and the work environment on employee performance proven results Fhitung> Ftable is 113.795> 3.00 and a value of 0.05 is 0.000 <0.05; 4) the coefficient of determination (R2) of 0.595 obtained show that the employee's performance is influenced by a combination of variables the welfare of employees and the work environment of 59.5% comprising 30.4% of the welfare of employees and 29.1% of the working environment and the remaining 40, 5% are influenced by variables studied. Keywords: Employee Performance, Employee Benefits, Work Environment